The Rhetorical Efforts of Sibweh - Shaker, Haidar S. (Humanities Journal of University of Zakho, 2013)
Thank Goa and peace be upon our messenger Muhammad and his companions and followers. The rhetorical efforts are considered one of the most important studies in all literary and linguistics field, for it provides of resources and knowledge that enables the rhetorical researchers to shied lights on important sides of the language and literature in general and the rhetoric especially. No linguistics book is free of important resources that participate in rhetorical research. Based on that I studied the rhetorical efforts of sibweh and the result was this research. The research focused on three investigations: preceded by an introduction and followed by conclusion. As for the preface, it shortly talks about the grammar science and the grammarian roles in the development of rhetorical science. The first investigation comes under the title the investigation of the science of meaning that sibweh had, the second investigation shows the science of statement, and the third one investigates in the science of Budaiya in rhetoric. As for conclusion, most important results of the research are discussed. The complexity of this subject had impact on the complexity of its resources in which were rhetoric, linguistic, and literary. The research aimed at showing the rhetorical efforts of a famous linguists, Sibweh. He is known for his authorship (Al-kitab). The research focused on his book (Al0kitab) which is regarded as one of the most remarkable resources that searched a lot in the rhetorical arts. It’s an important book for language and literature. Such researches are considered as an institutionalization for linguists’ efforts, they give them their leadership right, and highlights their roles. Regardless his roles in research on rhetorical art, linguists’ studies on both language and literature that passed through different centuries- their understanding of rhetorical art, and these efforts between our hand contributed into this subject and its considered beneficial especially for those who are interested and for all linguists. It forms one of the important lines in linguistics and its literature. Thank goes to those whom talked about the subject previously. I hope this study will be of benefit for those who study Arabic science, a modest service for the Holy book and our prophet sunnah peace be upon him and his companions and followers, and an effort that people make use of.